Strategies for Removing Endocrine Disrupting Chemicals (EDCs) from Wastewater - Sarkar, Sayanee; Zafar, Ayesha; Paul, Sourav; Das, Bishal; Biswas, Deepika; Panda, Jigisha Roy (Current Pharmaceutical Biotechnology, 2025)
Introduction Endocrine-disrupting drugs, also called endocrine disruptors or micropollutants, cause serious environmental and public health problems due to their ability to disrupt the endocrine functions of organisms and humans, even at low concentrations. This report provides a summary of current removal techniques, such as activated sludge processes, membrane filtration, adsorption, and membrane bioreactor techniques for endocrine-disrupting chemicals, including their efficiency, limitations, and practical implementation. Methods This review evaluates these methods by considering their treatment efficiency, costs, and environmental impact. To curb this menace, several developed countries have distinct strategies, such as physical remediation techniques, biological processes, phytoremediation, and chemical processes to remove endocrine disruptors. Results In developing nations, most conventional wastewater treatment plants do not even monitor those contaminants due to the low biodegradability and high complexity of such compounds. Conclusion Hence, in this review work, potential endocrine-disrupting chemicals, their impacts, mechanisms of action, consequences for human health, and bio-mitigation strategies reported so far have been discussed in the context of the relevant literature.
Keywords: high complexity